Anaplastic lymphoma kinase gene rearrangements in cytological samples of non–small cell lung cancer: Comparison with histological assessment. Issue 6 (19th March 2014) - Proietti, Agnese; Alì, Greta; Pelliccioni, Serena; Lupi, Cristiana; Sensi, Elisa; Boldrini, Laura; Servadio, Adele; Chella, Antonio; Ribechini, Alessandro; Cappuzzo, Federico; Miccoli, Mario; Fontanini, Gabriella
<x xml:space="preserve">Abstract</x> BACKGROUND Anaplastic lymphoma kinase (ALK) gene rearrangements are detected in approximately 5% of cases of non‐small cell lung cancer (NSCLC). Patients who are positive for ALK rearrangements may be successfully treated with the ALK inhibitor crizotinib. Because advanced‐stage lung cancers are not suitable for surgical resection, approximately 70% of patients are diagnosed via preoperative specimens. In the current study, the authors evaluated the suitability of stained cytologic direct smears and cell blocks for fluorescence in situ hybridization (FISH) to determine ALK status compared with small biopsies. METHODS A total of 493 consecutive patients with NSCLC were analyzed by FISH for ALK gene rearrangements. The analyzed sample comprised 180 cytological samples, 94 direct smears, 86 cell blocks, and 313 preoperative small biopsies. Moreover, in the same series, 426 patients and 369 patients, respectively, were evaluated for epidermal growth factor receptor and KRAS mutations, respectively. RESULTS Of the total of 493 patients, 18 patients who were positive for a gene rearrangement (4.4%) demonstrated ALK FISH rearrangements, whereas 387 patients (95.6%) were negative. All other cases were classified as inadequate (7.7%) and insufficient (10.1%). A strong statistical association was found between the cytology and the small biopsy with respect to ALK rearrangements (P = .0048). Fifty‐three patients (12.4%) demonstrated an epidermal growth factor receptor mutation, whereas 90 patients (24.4%) were found to have KRAS mutations. None of these patients presented with ALK gene rearrangements. CONCLUSIONS ALK gene rearrangements may be easily detected in cytological samples and particularly in direct smears, thereby yielding important improvements in the diagnostic approach to patients with advanced NSCLC. Cytological samples may be useful for ALK analysis when insufficient material is available in cell blocks or small biopsies. Cancer (Cancer Cytopathol) 2014;122:445–453. © 2014 American Cancer Society.